2020
DOI: 10.1007/s00784-020-03356-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a systematic digitized training program on the effectivity of subgingival instrumentation with curettes and sonic scalers in vitro

Abstract: Objectives Whereas the key role of subgingival instrumentation in periodontal therapy is well known, the influence of operators’ experience/training with different devices on treatment results is yet uncertain. Therefore, we assessed untrained undergraduate students, working on manikins, as to how effectively they learn to use curettes (GRA) and sonic scalers (AIR); hypothesizing that AIR will result in higher relative cleaning efficacy (RCE) than GRA. Material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, the participants in the CTP group preferred AIR for higher effectiveness. Previously, we found that the learning curve for RCE-b was steeper with AIR than with GRA in DTP [11]. Without training, only 27% of all the students reached a cleaning performance of at least 70% when using AIRs (GRA: 40%).…”
Section: Statementsmentioning
confidence: 88%
See 4 more Smart Citations
“…However, the participants in the CTP group preferred AIR for higher effectiveness. Previously, we found that the learning curve for RCE-b was steeper with AIR than with GRA in DTP [11]. Without training, only 27% of all the students reached a cleaning performance of at least 70% when using AIRs (GRA: 40%).…”
Section: Statementsmentioning
confidence: 88%
“…After 12 weeks (end of the training period), the effectiveness of all the participants (DTP/CTP) was evaluated, and their self-assessment was determined by questionnaire. During practical evaluation, 12 comparable test teeth had to be instrumented with GRA (tooth: 11,14,16,31,37,45) and with AIR (tooth: 21,25,17,34,36,43). The sequence of both instruments was initially randomized (Microsoft Excel 16, Microsoft Corporation, One Microsoft Way Redmond, WA, USA) for each participant.…”
Section: Student Training Program and Instrumentation Proceduresmentioning
confidence: 99%
See 3 more Smart Citations